Occupational Barriers and the Labor Market Penalty from Lack of Legal Status - Francesc Ortega; Amy Hsin (Institute of Labor Economics (IZA), 2018)
Wage gaps between documented (including natives) and undocumented workers may reflect employer exploitation, endogenous occupational sorting and productivity losses associated with lack of legal status. Identification of the undocumented productivity penalty is crucial to estimate the aggregate economic gains from legalization. This paper presents a new identification strategy based on the interplay between educational attainment and occupational barriers. Our main finding is that lack of legal status reduces the productivity of undocumented workers by about 12%. We also find that Dreamers are positively selected compared to similarly skilled natives, as one would expect if they face occupational barriers (Hsieh et al., 2013). Our estimates also imply that the degree of employer exploitation is likely to be small, suggesting that employer competition bids up the wages of undocumented workers and aligns them with their productivity. Last, we also find evidence suggesting that the occupational choices of undocumented workers are heavily influenced by licensing requirements and by the degree of exposure to apprehension by immigration enforcement agencies. In sum, our results strongly suggest that occupational barriers associated with lack of legal status lead to misallocation of talent and negatively affect economic growth.
Keywords: J15; J24; J31; 330; migration; undocumented; legalization; amnesty; dreamers